Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Comparative studies of different types of osteosynthesis on the human corpse preparation in bilateral antero-lateral flail chest - Grupp, Sina; Fürst, Veronika; Buder, Thomas; Fichte, Alexander; Krinner, Sebastian; Carbon, Roman T.; Hennig, Friedrich; Langenbach, Andreas; Schulz-Drost, Stefan (Injury-International Journal of the Care of the Injured, 2017)
Bilateral flail chest injuries are challenging in treatment and comparatively often require an operative stabilization of the anterior chest wall to re-establish normal physiological conditions of the chest wall in shape and statics. Various procedures have been described which are technically sophisticated for the surgeon. Consequently there is an increasing interest in potentials of operative care and their effectiveness on the anterolateral chest wall.12 Human cadavers were prepared and the natural Sternum Position (NP) was marked. A digital probe was fixed to the sternum at the height of the 4th intercostal space in order to measure and compare the stability of the thorax. Readings were taken of the sternal displacement at 1-5cm sagittal distance from NP in starting conditions and from every combination of materials. Serial osteotomies were performed on 2 locations on ribs 2-8 to induce bilateral flail chest. Afterwards the stabilization was achieved with different implants: RESULTS: The osteotomies lead to a subsidence of the sternum occurred to almost 75 mm from NP which corresponds to a maximal unstable situation. The unstable chest wall showed substantially more stabilization through the use of locking plates. Our materialcombinations showed a stability of up to 60% of normal. The more ribs were treated osteosynthetically, the higher the stability of the chest wall.Locking plate fixation offers anatomically realignment of the ribs whereas metal strut support only lifts up the chest wall, but could not provide realignment of the dislocated ribs.
EVALuna2:15857